LITERATURE REVIEW: FRESHWATER QUALITY AS A DETERMINANT OF SUSTAINABLE NILE TILAPIA (Oreochromis niloticus) AQUACULTURE: FOOD SECURITY POTENTIAL ON LOMBOK ISLAND, INDONESIA - Awan Dermawan; Abd Saddam Mujib (Universitas Mataram, 2026)
Tilapia (Oreochromis niloticus) aquaculture is an important source of animal protein with the potential to support local food security in island regions such as Lombok Island; however, the sustainability of its production is heavily influenced by the quality of the freshwater used as the aquaculture medium. This study aims to analyze the role of water quality as a determining factor for the sustainability of tilapia farming and its contribution to regional food security. The research was conducted using a systematic literature review approach with a PRISMA-based selection procedure for scientific publications since 2014. The synthesis results indicate that key water quality parameters, such as temperature, pH, dissolved oxygen, organic load, and nitrogen nutrient content, are consistently associated with the growth, health, and productivity of tilapia. Water quality degradation due to anthropogenic pressures has the potential to reduce the stability of aquaculture production and disrupt the availability of protein sources for the community. These findings underscore that water quality management is a key component of sustainable aquaculture systems and has strategic implications for efforts to strengthen local food security. This study provides a conceptual foundation for integrating water management policies with the development of adaptive and sustainable tilapia aquaculture.